Pengembangan Leaflet Digital Berbasis Kearifan Lokal Bangka Belitung pada Materi Jenis-jenis Pekerjaan Kelas IV - Indah Resta, Offie; Yurdayanti; Martahayu, Vika (JBES (Journal Basic Education Skills), 2025)
The absence of technology and local wisdom-based learning in Bangka Belitung is the driving force for this research because it makes students feel passive in the learning process, especially in terms of the type of work they are required to do. Therefore, it is very important to create a digital pamphlet about class IV employment that is based on the local wisdom of Bangka Belitung and is original and useful. Analysis, design, development, implementation and evaluation are the five steps of the ADDIE paradigm which are used in the form of studies known as research and development (R&D). At SDN 9 Simpang Rimba, 26 grade IV students and their teachers were used as research subjects. The instruments and procedures used in data collection include surveys and interviews. Experts in the field of media and materials science carry out quantitative descriptive data analysis, specifically focusing on the veracity of the data. Practicality data was collected through interviews and questionnaire analysis findings. The media validator received a score of 100% (Very Valid) and the material validator received a score of 86% (Very Valid) based on the evaluation findings. Large group trials provide 100% results (Very Practical), as well as small group trials with 100% results (Very Practical). 100% of teachers answered the questionnaire (very practical). Therefore, the digital pamphlet for class IV elementary school assignments based on Bangka Belitung local wisdom can be said to be very reliable and useful.